2005
DOI: 10.1016/j.ydbio.2004.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Wnt and caudal-related genes in zebrafish posterior body formation

Abstract: Although Wnt signaling plays an important role in body patterning during early vertebrate embryogenesis, the mechanisms by which Wnts control the individual processes of body patterning are largely unknown. In zebrafish, wnt3a and wnt8 are expressed in overlapping domains in the blastoderm margin and later in the tailbud. The combined inhibition of Wnt3a and Wnt8 by antisense morpholino oligonucleotides led to anteriorization of the neuroectoderm, expansion of the dorsal organizer, and loss of the posterior bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
214
0
2

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 186 publications
(229 citation statements)
references
References 89 publications
13
214
0
2
Order By: Relevance
“…Further supporting this hypothesis, TCF-dependent reporter activity and the nuclear localization of endogenous b-catenin are elevated in the anterior-toposterior gradient (Kiecker and Niehrs 2001;Dorsky et al 2002). The critical role of Wnt signaling in anteroposterior axis specification has been corroborated by depletion experiments for pathway components Erter et al 2001;Lekven et al 2001;Shimizu et al 2005;Bellipanni et al 2006;Hikasa et al 2010) and the analysis of the corresponding zebrafish mutations. Headless (hdl) was identified as a point mutation in a tcf3 gene homolog, which represses Wnt target genes in zebrafish embryos (Kim et al 2000).…”
Section: Zygotic Wnt Signaling During Anteroposterior Axis Specificationmentioning
confidence: 87%
“…Further supporting this hypothesis, TCF-dependent reporter activity and the nuclear localization of endogenous b-catenin are elevated in the anterior-toposterior gradient (Kiecker and Niehrs 2001;Dorsky et al 2002). The critical role of Wnt signaling in anteroposterior axis specification has been corroborated by depletion experiments for pathway components Erter et al 2001;Lekven et al 2001;Shimizu et al 2005;Bellipanni et al 2006;Hikasa et al 2010) and the analysis of the corresponding zebrafish mutations. Headless (hdl) was identified as a point mutation in a tcf3 gene homolog, which represses Wnt target genes in zebrafish embryos (Kim et al 2000).…”
Section: Zygotic Wnt Signaling During Anteroposterior Axis Specificationmentioning
confidence: 87%
“…Other studies have suggested that Wnt signaling prevents posterior mesoderm progenitor differentiation, thereby maintaining a posterior mesoderm progenitor pool (Shimizu et al, 2005;Thorpe et al, 2005;Martin and Kimelman, 2008;Row and Kimelman, 2009). This suggests an additional role for wnt8 wherein BMPs are necessary for the maintenance of the tailbud, but the release of progenitors into presomitic mesoderm is a Wntregulated process.…”
Section: Wnt8 Bmp and Ventrolateral Mesoderm Patterningmentioning
confidence: 99%
“…The mesodermal phenotype of wnt8 mutants could be explained by two alternative hypotheses: on the one hand, mesoderm dorsalization may result in specification of fewer ventrolateral/posterior mesoderm progenitors, thereby restricting the progenitor pool that contributes to ventral and posterior fates. On the other hand, Wnt signaling may have a role in promoting the maintenance or expansion of posterior mesoderm progenitors, for example through cdx or no tail/brachyury gene regulation (Shimizu et al, 2005;Thorpe et al, 2005;Martin and Kimelman, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The Cdx (caudal) and the Meis group genes, like Vent genes, are regulated by Wnt signaling during anteroposterior patterning [129][130][131] and contain multiple TCF-binding sites in their DNA regulatory elements [132][133][134]. Like Vent genes, these genes are also controlled by TCF3-mediated repression [79].…”
Section: Mechanisms Of Target Gene Regulationmentioning
confidence: 99%